?CHARACTERIZATION OF SPRING WATERS OF MURREE REGION (Biological Sciences - PJSIR, 2000)
Tensamplesof waterfromspringslocatedin differentpartsofMurreeregionofPakistan werecollected andevaluated for thedrinking quality.The chemical analysisshowedthatall samplesareofthe sametype andare fit fordrinking, domestic or industrial purposes as these fall within the WHO permissible limits of drinking water.Two samples were better than others due to low hardness and alkalinity whereasone sample hadthe highest hardness and alkalinity.